2012
DOI: 10.1371/journal.ppat.1002484
|View full text |Cite
|
Sign up to set email alerts
|

The Viral and Cellular MicroRNA Targetome in Lymphoblastoid Cell Lines

Abstract: Epstein-Barr virus (EBV) is a ubiquitous human herpesvirus linked to a number of B cell cancers and lymphoproliferative disorders. During latent infection, EBV expresses 25 viral pre-microRNAs (miRNAs) and induces the expression of specific host miRNAs, such as miR-155 and miR-21, which potentially play a role in viral oncogenesis. To date, only a limited number of EBV miRNA targets have been identified; thus, the role of EBV miRNAs in viral pathogenesis and/or lymphomagenesis is not well defined. Here, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
465
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 312 publications
(501 citation statements)
references
References 84 publications
(186 reference statements)
20
465
1
1
Order By: Relevance
“…Finally, we used 10 internally generated Ago-CLIP-seq samples (HPNE and MIA PaCa-2 cells and human brain tissue) and combined them with an additional 33 public datasets from HEK293 cells (46), LCLs (47), and human brain (48) (Dataset S1). Each mature miRNA candidate had to completely coincide with an Ago CLIP-seq site, be observed in at least 1 of the 43 CLIP-seq samples, and be supported by five or more unambiguously mapped CLIP-seq reads.…”
Section: Identification Of Significantly Expressed Sample-dependent Nmentioning
confidence: 99%
“…Finally, we used 10 internally generated Ago-CLIP-seq samples (HPNE and MIA PaCa-2 cells and human brain tissue) and combined them with an additional 33 public datasets from HEK293 cells (46), LCLs (47), and human brain (48) (Dataset S1). Each mature miRNA candidate had to completely coincide with an Ago CLIP-seq site, be observed in at least 1 of the 43 CLIP-seq samples, and be supported by five or more unambiguously mapped CLIP-seq reads.…”
Section: Identification Of Significantly Expressed Sample-dependent Nmentioning
confidence: 99%
“…The roles of these BHRF1 miRNAs were unclear until recent in vitro studies using viral knockouts in lymphoblastoid cell lines (LCLs), a widely used cellular model of latency III EBV infection, revealed that the BHRF1 miRNAs cooperate to enhance B cell expansion, reduce levels of latent gene expression, and possibly also inhibit apoptosis (10-12). Additionally, as circumstantial evidence for the roles of these miRNAs, studies that comprehensively examined the targets of EBV miRNAs have shown that BHRF1 miRNAs bind a number of targets involved in proliferation, latent gene expression, and regulation of apoptosis (13,14).…”
Section: Over 90% Of the Adult Human Population Is Chronically Infectmentioning
confidence: 99%
“…There are an increasing number of viral miRNAs that contain seed sequences identical to known cellular miRNAs. For example, the EBV miRNAs miR-BART1 and miR-BART3, which have seed sequences either identical to miR-B4 and miR-29 (miR-BART1) or offset by one nucleotide from the miR-B4 and miR-29 seed (miR-BART3), have recently been shown to share a number of mRNA targets with miR-29 (17). EBV is also an established transforming virus in human B cells, so the importance of viral mimics of cellular miRNAs in viral tumorigenesis in general, and of viral analogs of miR-29 in B-cell lymphoma in particular, certainly merits additional investigation.…”
mentioning
confidence: 99%